2022
DOI: 10.1101/gr.277118.122
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, duplication, and genomic organization of homeobox genes in Lepidoptera

Abstract: Homeobox genes encode transcription factors with essential roles in patterning and cell fate in developing animal embryos. Many homeobox genes, including Hox and NK genes, are arranged in gene clusters, a feature likely related to transcriptional control. Sparse taxon sampling and fragmentary genome assemblies mean that little is known about dynamics of homeobox gene evolution across Lepidoptera, or how changes in homeobox gene number and organization relate to diversity in this large order of insects. Here we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 103 publications
(159 reference statements)
0
10
0
Order By: Relevance
“…It exhibits aberrations in the transcriptional orientation of some genes as well as both interspersed genes of independent origin and Hox-derived genes that have evolved novel developmental functions 11 . Additional Hox cluster rearrangements have also been reported in other Drosophila species 16,22,66,67 as well as in the silk moth Bombyx mori 68 . The rearrangement of Hox genes in the Cluster of C. elegans has also been reported before 29 .…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…It exhibits aberrations in the transcriptional orientation of some genes as well as both interspersed genes of independent origin and Hox-derived genes that have evolved novel developmental functions 11 . Additional Hox cluster rearrangements have also been reported in other Drosophila species 16,22,66,67 as well as in the silk moth Bombyx mori 68 . The rearrangement of Hox genes in the Cluster of C. elegans has also been reported before 29 .…”
Section: Discussionmentioning
confidence: 74%
“…The Hox cluster in Drosophila melanogaster is split into two subclusters 21 . Splitting has occurred repeatedly and independently in other Drosophilids, at different positions along the cluster 16,22 . Disaggregation of the Hox cluster can be observed in tunicate chordates Ciona intestinalis (solitary tunicate) and Oikopleura dioica (appendicularian) where Hox loci are present but not tightly linked in the genome 23,24 .…”
Section: Introductionmentioning
confidence: 99%
“…While the NK genes in different drosophilid species have undergone a series of rearrangements, fragmenting and then reuniting the NK cluster, certain gene pairs or triplets are consistently clustered and move as units referred to as “contiguities” (Chan et al 2015). In spiders, NK3 and NK4 are adjacent, as in D. melanogaster , T. castaneum , Bombyx terrestris , many butterflies, and Anopheles gambiae , and Tlx and Lbx are adjacent, as in D. melanogaster , T. castaneum , several butterflies, A. gambiae and I. scapularis (Figure 4) (Luke et al 2003; Chan et al 2015; Mulhair et al 2022). Though NK1 has undergone a recent tandem duplication in spiders, NK5 and NK1 are also adjacent in T. castaneum , B. terrestris , A. gambiae , and I. scapularis , but not D. melanogaster or butterflies (Figure 4) (Chan et al 2015; Mulhair et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Although the developmental toolkit genes were once thought to be largely conserved among animals, recent genomic studies and curated annotations have revealed that lineage-specific and fast-evolving transcription factors are expressed during animal development (Holland et al, 2017), including in mammals (Lewin et al, 2021(Lewin et al, , 2022Maeso et al, 2016), echinoderms (Dylus et al, 2016;Yamazaki et al, 2020), lepidopterans (Chai et al, 2008;Ferguson et al, 2014;Mulhair et al, 2023), spiders (Iwasaki-Yokozawa et al, 2022), and spiralians (Morino, 2022;Morino et al, 2017;Paps et al, 2015;Phuangphong et al, 2021). In the examples above, most transcription factors are expressed zygotically and function early in animal development.…”
Section: Introductionmentioning
confidence: 99%